2016
DOI: 10.7150/jca.16539
|View full text |Cite
|
Sign up to set email alerts
|

Multidimensional Roles of Collagen Triple Helix Repeat Containing 1 (CTHRC1) in Malignant Cancers

Abstract: Tumor is one of the principal diseases that seriously threaten human health. Insight into sensitive cancer markers may open a new avenue for the early diagnosis and treatment of this disease. CTHRC1 has been identified as a cancer-related gene. It is a secretory glycoprotein that possesses multidimensional roles associated with wound repair, bone remodeling, hepatocytes fibrosis, adipose tissue formation, and so on. Our previous studies and numerous reports from other researchers have revealed that the ascende… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(15 citation statements)
references
References 71 publications
1
14
0
Order By: Relevance
“…Thus, we concluded that miR-155-5p negatively mediated tumor growth and metastasis of HCC in vitro by CTHRC1 modulation. Furthermore, a great deal of literature has demonstrated that the elevated expression of CTHRC1 was ubiquitously associated with cancer proliferation, invasion, migration, adhesiveness and metastasis and ultimately contributed to the initiation, promotion and progression of cancers, including pancreatic cancer, epithelial ovarian cancer, non-small cell lung cancer and colorectal cancer [ 33 ], which further validated our above stated conclusion. Finally, a xenograft model of BALB/c nude mice was established to certify the impacts of miR-155-5p and CTHRC1 on tumor formation in vivo.…”
Section: Discussionsupporting
confidence: 77%
“…Thus, we concluded that miR-155-5p negatively mediated tumor growth and metastasis of HCC in vitro by CTHRC1 modulation. Furthermore, a great deal of literature has demonstrated that the elevated expression of CTHRC1 was ubiquitously associated with cancer proliferation, invasion, migration, adhesiveness and metastasis and ultimately contributed to the initiation, promotion and progression of cancers, including pancreatic cancer, epithelial ovarian cancer, non-small cell lung cancer and colorectal cancer [ 33 ], which further validated our above stated conclusion. Finally, a xenograft model of BALB/c nude mice was established to certify the impacts of miR-155-5p and CTHRC1 on tumor formation in vivo.…”
Section: Discussionsupporting
confidence: 77%
“…Next, we assessed whether pirfenidone altered the expression of targets related to TGF-β1-mediated fibrotic processes in HFL-1 cells. As CTHRC1 and FHL2 are located both in the cytoplasm and nucleus [32, 33], we evaluated the effects of pirfenidone on the localization of the TGF-β1-induced fibrosis regulators using immunofluorescence analysis. TGF-β1 strongly enhanced both CTHRC1 and FHL2 staining, whereas pirfenidone suppressed TGF-β1-induced CTHRC1 and FHL2 expression, including the nuclear localization (fluorescein isothiocyanate stain; green immunofluorescence: Fig.…”
Section: Resultsmentioning
confidence: 99%
“…CTHRC1 (collagen triple helix repeat-containing 1), a 30 kDa glycosylated protein, was first identified in the healing process of injured arteries [22]. There has been a growing enthusiasm for targeting CTHRC1 in the progression and metastasis of various cancers, including NSCLC [23,24,25,26]. For example, CTHRC1 expression at both mRNA and protein levels was significantly higher in NSCLC tumor cells than in adjacent noncancerous tissues [27]; increased serum CTHRC1 has been found in NSCLC patients and positively correlated with metastasis [28]; and CTHRC1 promotes NSCLC cell proliferation and motility, and could be a biomarker of poor prognosis for NSCLC patients [27].…”
Section: Introductionmentioning
confidence: 99%